Is it possible for leading companies to affect the control system of their subsidiaries? - Margarida Rodrigues; Maria Do Céu Alves; Cidália Oliveira; Amélia Ferreira da Silva; Rui Silva (Cogent Business & Management, 2023)
Management Control Systems (MCS) have become increasingly important for the management of subsidiaries by the parent company. In addition, MCS are influenced by the cultural and organizational axes of both parties (parent company vs. subsidiaries).Therefore, an appropriate balance between these axes is required since there are differences between the country of origin and the host country of the investment. Thus, this study explores the MCS of a subsidiary and the parent company's influences on it through a case study supported by multiple semi-structured interviews. The results obtained show that the parent company exerts a strong influence on the MCS of the subsidiary. This assertiveness is revealed in the subsidiary's weak operational and non-operational autonomy as a reflection of the parent company's organisational culture (country of origin of the investment). The main contribution of this study lies in the country of origin of the parent company (Asia) and in the study of an extractive industry whose end product (tungsten) is a strategic resource for the world. Another contribution is theoretical and related to the new institutional sociology. This theory recognizes the normative and cultural issues of organizations as essential and sees management accounting practices and management control systems as the result of internal and external pressures, as well as the growing importance given to the norms, beliefs, and values of stakeholders within the organization and the organizational environment itself. The use of the Flamholtz model applied to the mining sector also fills a gap identified in the literature.
Keywords: 650; autonomy; management control tool; multinational; organisational culture; subsidiary